2017
DOI: 10.1142/s0218127417500687
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate Fold–Hopf Bifurcations in a Rössler-Type System

Abstract: We study the Hopf and the fold–Hopf bifurcations of the Rössler-type differential system [Formula: see text] with [Formula: see text]. We show that the classical Hopf bifurcation cannot be applied to this system for detecting the fold–Hopf bifurcation, which here is studied using the averaging theory. Our results show that a Hopf bifurcation takes place at the equilibrium [Formula: see text] when [Formula: see text]. This Hopf bifurcation becomes a fold–Hopf bifurcation when [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The normal form equations for degenerate ZH bifurcations are not well known and previous studies have focused on different cases [73,74]. Tigan et al [75] showed that a degenerate ZH bifurcation with G 011 (0) ¼ 0 occurs in a Rö ssler-type system and used averaging theory to detect periodic orbits, leaving the structure of global bifurcations unresolved. We believe, as far as we know, that this is the first time a curve of TPO bifurcations has been observed to emanate from a degenerate ZH bifurcation of this type.…”
Section: Appendix a Further Study Of Degenerate Bogdanov -Takens And Zero-hopf Bifurcationsmentioning
confidence: 99%
“…The normal form equations for degenerate ZH bifurcations are not well known and previous studies have focused on different cases [73,74]. Tigan et al [75] showed that a degenerate ZH bifurcation with G 011 (0) ¼ 0 occurs in a Rö ssler-type system and used averaging theory to detect periodic orbits, leaving the structure of global bifurcations unresolved. We believe, as far as we know, that this is the first time a curve of TPO bifurcations has been observed to emanate from a degenerate ZH bifurcation of this type.…”
Section: Appendix a Further Study Of Degenerate Bogdanov -Takens And Zero-hopf Bifurcationsmentioning
confidence: 99%